Development of Mathematics Learning Media Using STEM Approach to Linear Program Materials - Aprilia, Eka; Pujiastuti, Heni; Rafianti, Isna (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2021)
This study aims to develop mathematics learning media with a STEM approach to linear program material that is valid, practical, and has a potential effect on student responses. This development research uses a research design that is a design research development study type. The research subjects were students of class XI MIPA 5 at SMA Negeri 14 Kota Tangerang. The research subjects were students of class XI MIPA 5 at SMA Negeri 14 Kota Tangerang. Based on the research results, the learning media is suitable for use in the learning process because it fulfills the indicators of validity, practicality, and potential effects. The validity of learning media based on the evaluation of education experts is 86% and the evaluation of media experts is 86%. The practicality of learning media is 94%. The potential effect of learning media is seen from the student's response by 95%.Penelitian ini bertujuan untuk mengembangkan media pembelajaran matematika dengan pendekatan STEM pada materi program linear yang valid, praktis, dan memiliki efek potensial terhadap respon siswa. Penelitian pengembangan ini menggunakan desain penelitian yaitu design research tipe development study. Subjek penelitian adalah siswa kelas XI MIPA 5 di SMA Negeri 14 Kota Tangerang. Berdasarkan hasil penelitian, media pembelajaran layak untuk digunakan dalam proses pembelajaran karena memenuhi indikator kevalidian, kepraktisan, dan efek potensial. Kevalidan media pembelajaran berdasarkan penilaian ahli pendidikan sebesar 86% serta penilaian dari ahli media sebesar 86%. Kepraktisan media pembelajaran sebesar 94%. Efek potensial media pembelajaran dilihat dari respon siswa sebesar. 95%.